Wnt/β-catenin Signaling Pathway Regulates Specific lncRNAs That Impact Dermal Fibroblasts and Skin Fibrosis - Mullin, Nathaniel K.; Mallipeddi, Nikhil V.; Hamburg-Shields, Emily; Ibarra, Beatriz; Khalil, Ahmad M.; Atit, Radhika P. (Frontiers in Genetics, 2017)
Wnt/β-catenin signaling is required for embryonic dermal fibroblast cell fate, and dysregulation of this pathway is sufficient to promote fibrosis in adult tissue. The downstream modulators of Wnt/β-catenin signaling required for controlling cell fate and dermal fibrosis remain poorly understood. The discovery of regulatory long non-coding RNAs (lncRNAs) and their pivotal roles as key modulators of gene expression downstream of signaling cascades in various contexts prompted us to investigate their roles in Wnt/β-catenin signaling. Here, we have identified lncRNAs and protein-coding RNAs that are induced by β-catenin activity in mouse dermal fibroblasts using next generation RNA-sequencing (RNA-seq). The differentially expressed protein-coding mRNAs are enriched for extracellular matrix proteins, glycoproteins, and cell adhesion, and many are also dysregulated in human fibrotic tissues. We identified 111 lncRNAs that are differentially expressed in response to activation of Wnt/β-catenin signaling. To further characterize the role of mouse lncRNAs in this pathway, we validated two novel Wnt signaling- Induced Non-Coding RNA (Wincr) transcripts referred to as Wincr1 and Wincr2. These two lncRNAs are highly expressed in mouse embryonic skin and perinatal dermal fibroblasts. Furthermore, we found that Wincr1 expression levels in perinatal dermal fibroblasts affects the expression of key markers of fibrosis (e.g. Col1a1 and Mmp10), enhances collagen contraction, and attenuates collective cell migration. Our results show that β-catenin signaling-responsive lncRNAs may modulate dermal fibroblast behavior and collagen accumulation in dermal fibrosis, providing new mechanistic insights and nodes for therapeutic intervention.